Revealing orbital and magnetic phase transitions in Pr0.5Ca0.5MnO3 epitaxial thin films by resonant soft x-ray scattering - H Wadati; J Geck; E Schierle; R Sutarto; F He; D G Hawthorn; M Nakamura; M Kawasaki; Y Tokura; G A Sawatzky (New Journal of Physics, 2014)
We report the study of magnetic and orbital order in ${{\Pr }_{0.5}}$ ${\text{Ca}_{0.5}}$ ${\text{MnO}_{3}}$ epitaxial thin films grown on ${{({\text{LaAlO}_{3}})}_{0.3}}$ – $({\text{SrAl}_{0.5}}$ ${\text{Ta}_{0.5}}$ ${{\text{O}}_{3}}{{)}_{0.7}}$ . Resonant soft x-ray scattering revealed significant modifications of the magnetic order in the film as compared to the bulk. Namely (i) a different magnetic ordering wave vector, (ii) different spin directions and (iii) an additional magnetic reordering transition. We demonstrate that an analysis of the resonant scattering which is based solely on local symmetries and which does not involve a modeling of energy-dependent lineshapes allows to extract this detailed microscopic information. This approach significantly simplifies the analysis and interpretation of resonant scattering data.